Clinical outcome and quality of life after gracilis muscle transposition for fistula closure over a 10-year period - Grott, Matthias; Rickert, Alexander Lothar; Hetjens, Svetlana; Kienle, Peter (International journal of colorectal disease, 2021)
Gracilis muscle transposition (GMT) is an established surgical technique in the treatment of anorectal fistulas and fistulas to the vagina and the urinary system when previous closure options have failed. There is little evidence on the success rate of this procedure in the long term.